A Context-Aware Mobile-Based System for Crime Prevention and Emergencies - Sarifah Putri Raflesia; Taufiqurrahman Taufiqurrahman; Dinda Lestarini; Ali Bardadi (IAES Indonesian Section, 2021)
Crime is a global issue that arises as a consequence of social problems in society such as poverty and densely population due to urbanization. In large cities, governments have applied technology to support crime prevention. In this paper, a mobile-based system is proposed to increase knowledge and public awareness which may reduce the risk of crimes. A context-aware system, namely, geo-fence, is used to enable virtual fences around crime hotspots. Crime hotspots are determined using crime histories and crowd-sourced data provided by citizens. As citizens enter crime hotspots, they would be alerted and provided information. Meanwhile, if they find or experience crime, they are able to report and label the location of the crime.